Relevance of hippocampal integrity for memory outcome after surgical treatment of mesial temporal lobe epilepsy - Witt, Juri-Alexander; Coras, Roland; Schramm, Johannes; Becker, Albert J.; Elger, Christian E.; Blümcke, Ingmar; Helmstaedter, Christoph (Journal of Neurology, 2015)
Surgical treatment of unilateral mesial temporal lobe epilepsy (mTLE) particularly bears the risk of episodic memory decline. The present study investigates the role of the ipsilateral hippocampal integrity for postoperative change in material-specific memory performance. In 104 patients who had undergone epilepsy surgery for unilateral mTLE, we analyzed pre- to postoperative changes of verbal and figural memory as a function of segmental neuronal cell densities of the resected hippocampus (cornu ammonis, CA1-4; internal and external limb of the dentate gyrus, DG). Results were controlled for side of surgery and hemispheric dominance. Surgery caused significant memory decline, especially with regard to verbal memory after left temporal resections. Seizure freedom (65 % Engel Ia) did not affect memory outcome. Higher neuronal cell densities of the resected left hippocampus were associated with greater declines in verbal memory parameters (r = -0.27 to r = -0.39, p < 0.05), especially when excluding patients with atypical hemispheric dominance (r = -0.34 to r = -0.60, p < 0.05; significant correlations across all hippocampal subfields). There were no systematic correlations between neuronal cell densities of the resected right hippocampus and memory changes. The results emphasize the role of the structural and functional integrity of the hippocampus within the left dominant hemisphere for the degree of verbal memory decline after temporal lobe surgery. Presurgical verbal memory performance may be taken as a marker of ipsilateral left hippocampal integrity and may contribute to individual risk-benefit evaluations before epilepsy surgery. Finally, more precise neuropsychological markers of right hippocampal integrity are needed.
EVALuna2:7299